The interaction of DIAP1 with dOmi/HtrA2 regulates cell death in Drosophila. - Khan, F.S.; Fujioka, M.; Datta, P.; Fernandes-Alnemri, T.; Jaynes, J.B.; Alnemri, E.S. (Cell Death and Differentiation, 2008)
Mitochondrial proteins such as cytochrome c, Smac/DIABLO and Omi/HtrA2 play important roles in the cell death pathways of mammalian cells. In Drosophila, the role of mitochondria in cell death is less clear. Here, we report the identification and characterization of the Drosophila ortholog of human Omi/HtrA2. We show that Drosophila Omi/HtrA2 is imported into the mitochondria where it undergoes proteolytic maturation to yield two isoforms, dOmi-L and dOmi-S. dOmi-L contains a canonical N-terminal IAP-binding motif (AVVS), whereas dOmi-S contains a distinct N-terminal motif (SKMT). DIAP1 was able to bind to both isoforms via its BIR1 and BIR2 domains. This resulted in cleavage of the linker region of DIAP1 between the BIR1 and BIR2 domains and further degradation of the BIR1 domain by the proteolytic activity of dOmi. The binding of DIAP1 to dOmi also resulted in DIAP1-mediated polyubiquitination of dOmi, suggesting that DIAP1 could target dOmi for proteasomal degradation. Consistent with this, expression of DIAP1 in Drosophila eye discs protected them from dOmi-induced eye ablation, indicating that DIAP1 plays an important role in protecting cells from the potentially lethal effects of dOmi. The ability of IAPs to bind to and ubiquitinate mitochondrial proteins such as dOmi may be a key conserved function to counterbalance the lethal effects of these proteins if accidentally released into the cytosol.